FENOMENA PERILAKU BUANG AIR BESAR SEMBARANGAN DILATARBELAKANGI KARAKTERISTIK INDIVIDU DAN LINGKUNGAN SOSIAL - Sandi, William Ari; Febriana, Indah (Jurnal Pendidikan Kesehatan (e-Journal), 2023)
Growing up in a safe and clean environment is everyone's right. More than half of the world's population does not have access to safe and healthy sanitation. As many as 3 billion people do not have access to personal hygiene practices, and as many as 673 million people still practice open defecation. The purpose of the study was to determine the relationship between knowledge, attitudes, social support, the role of officers and special culture on open defecation behavior in the Sukaraja Health Center working area in 2022. This type of research is quantitative, with a cross sectional approach design. The study population was all heads of families living in the coastal area of the Sukaraja Health Center working area, a total of 2,050 families. The number of samples is 95 heads of families or communities. The results of the chi square test state that knowledge has a p-value of 0.032, community attitudes p-value 0.011, social support p-value 0.049, the role of health workers p-value 0.013, and special cultures have a p-value of 0.07 which means there is a relationship with open defecation behavior in the coastal area of the Sukaraja Public Health Center in 2022. Suggestions for puskesmas, officers need to improve monitoring, education and triggering to stop open defecation, and for community leaders to be able to actively provide support in encouraging community participation in triggering activities to stop open defecation.